Ovarian vein sampling, and serum and urine testosterone monitoring in ovarian Leydig cell tumors: A report of two cases - Whiteley, Grace (Case Rep Womens Health, 2019)
BACKGROUND: Ovarian Leydig cell tumors are rare, testosterone-producing tumors that pose diagnostic challenges. CASES: A 36-year-old woman presented with 10 years of amenorrhea, facial hair growth and clitoromegaly. A 59-year-old woman presented after 2 years of voice deepening and terminal hair growth. Testosterone concentrations were elevated for both patients; however, imaging failed to identify ovarian or adrenal pathology. For the first patient, selective ovarian venous sampling was performed with results suggesting right ovarian testosterone production. Right ovarian Leydig cell tumors were found in both patients after salpingo-oophorectomy. Testosterone levels immediately declined following tumor removal. CONCLUSION: Additional diagnostic modalities, such as ovarian venous sampling, should be considered when the etiology of hyperandrogenism cannot be identified through lab work or imaging. In addition, sequential post-operative testosterone levels in serum or urine can help confirm adequate removal of the ovarian tumor.